Konsep Harta dan Kepemilikan dalam Islam: Kajian Tafsir Tematik QS. At-Taubah Ayat 60 dan 103 - Elpianti Sahara Pakpahan; Yola Yulita; Hamdi Dermawan (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2026)
The concept of wealth ownership in Islam has been widely discussed in the fields of Islamic economics and Qur'anic studies. However, most previous studies focus separately on the legal aspects of zakat or the economic function of wealth, while limited attention has been given to the integrated interpretation of wealth ownership based on Surah At-Taubah verses 60 and 103 using a thematic (tafsir maudhu'i) approach. This study aims to analyze the concept of wealth ownership in Islam by examining these two verses to reveal the relationship between ownership rights, social responsibility, and spiritual purification. The research employs a qualitative library research method with a thematic interpretation (tafsir maudhu'i) approach. The findings demonstrate that Surah At-Taubah verses 60 and 103 establish an integrated framework of wealth ownership in which individual ownership is recognized but remains conditional upon fulfilling social obligations through zakat. Verse 60 identifies eight categories of zakat beneficiaries, thereby defining the social redistribution mechanism of wealth, while verse 103 positions zakat as an instrument for both material redistribution and spiritual purification of wealth owners. These findings contribute to the literature by offering a comprehensive interpretation that integrates the legal, social, and spiritual dimensions of wealth ownership within a single Qur'anic framework, providing a broader understanding of the Islamic concept of property rights.